(untitled) - Donnithorne, Audrey (London, 1958)
Contents: An outline of the structure of the bristish rubber manufactoring industry, Developments in rubber compounding, Synthetic rubber, Tyres and tubes, Rubber footwear, Latex-General, Latex foam and other cellular rubbers, dipped goods,....
Keywords: Rubber industry and trade,Công nghiệp cao su và thương mại; Great Britain